A STUDY ON THE PYROLYSIS OF PEANUT SHELLS AT DIFFERENT ISOTHERMAL CONDITIONS AND DETERMINATION OF THE KINETIC PARAMETERS - Tasar, Seyda; Kaya, Fatih; Ozer, Ahmet (Pamukkale Univ, 2015)
The pyrolysis process, which is applied for the aim of producing energy and raw materials which are implemented for the chemical industry from biomass sources, is a thermal conversion process. Determination of the pyrolysis kinetic parameters are important In order to suitable equipment and process design. In this target, in the study the pyrolysis of peanut shells was conducted in a muffle furnace at static atmosphere with temperatures ranging from 300-700 degrees C. The effects of various parameters on the rate of thermal decomposition rate and the solid yield were determined. The parameters of interest were temperature 300-700 degrees C, particle size 4-50 mesh, pelletizing, and pelletizing pressure 1.103-5.103 kgf/cm(2). Regression coefficients for the total decomposition step were obtained using the thermographs were obtained as a result of the pyrolysis of the peanut shells, and 20 different theoretical model equations that represented the degradation by the Coast-Redfern method. According to regression coefficients of the theoretical model equations, we determined the kinetic model that best represented the degradation. Using this model to represent the degradation, the activation energy (Ea) and Arhenius frequency factor ln(A) for the total reaction were calculated to be 38.245 kJ/mol and 8.124, respectively.
Keywords: Peanut shells; Pyrolysis; Kinetics; Pelletizing; Particle size